Efficacy and Safety for the Use of Half-Dosed Pegylated Granulocyte Colony-Stimulating Factors in Preventing Febrile Neutropenia During Chemotherapy in Patients With Malignant Tumors: A Multicenter, Open-Labeled, Single-Arm Phase 2 Trial - Mei, Qi; Li, Xiaoyu; Wang, Runkun; Qin, Kai; Cheng, Yi; Cheng, Weiting; Dong, Youhong; He, Zhen; Li, Jun; Li, Ming; Tang, Xi; Wang, Xudong; et al. (Frontiers in Oncology, 2022)
Background: Prophylactic G-CSF has been shown to effectively prevent febrile neutropenia (FN) and grade ¾ neutropenia during myelosuppressive treatment. The present study reports the clinical efficacy and safety of the prophylactic use of G-CSF with a half-dose for cancer patients with an intermediate risk of FN combined with ≥ 1 patient-specific risk during multiple chemotherapy. Methods: this multi-center, one-arm and open-label clinical study involved 151 patients (median age 54 years old [range 46.0-62.5]; 38.4% female) with malignant tumors, including > 20 different cancers. These patients underwent a total of 604 cycles of chemotherapy and received a half-dose of PEG-rhG-CSF administration prior to each cycle. Results: the incidence rate of FN was 3.3% for this cohort during chemotherapy. Chemotherapy delay occurred in 6 (4.0%) patients for 12 (2.0%) cycles. Early termination of cancer treatment occurred in 14 (9.3%) patients. In this cohort, 23 (15.2%) patients required for antibiotic use during courses of chemotherapy. A total of 28 (18.5%) patients experienced clear adverse effects during cancer treatment. Conclusion: the prophylactic PEG-rhG-CSF with a half-dose can both efficaciously and safely prevent neutropenia for patients of diverse cancers with an intermediate risk of FN combined with ≥ 1 patient-specific risk during chemotherapy.